The Implementation Of Cleaner Production Practices From Malaysian Manufacturers Perspectives - Yusup, Muhamad Zaki; Wan Mahmood, Wan Hasrulnizzam; Salleh, Mohd Rizal; Ab Rahman, Mohd Nizam (ELSEVIER, 2015)
-